THE EFFECTIVENESS OF SOCRATIVE APPLICATION FOR FORMATIVE ASSESSMENT ON THE EIGHTH GRADE STUDENTS IN TEACHING VOCABULARY AT SMPN 16 KOTA TANGERANG SELATAN - Hana Nabila; M Abduh Al-Manar; Yudhie Indra Gunawan (Universitas Muhammadiyah Tangerang, 2023)
The aim of the research is to investigate whether Socrative application is effective to be used on the Eighth Grade Students in learning vocabulary at SMPN 16 Kota Tangerang Selatan in the academic year 2021/2022. The participants of this research were 64 students, which were classified into the controlled class and the experimental class through saturation sampling technique. The design used was quasi-experimental study and the instrument of this research was test that consisted of pre-test and post- test. The result can be seen that using Socrative application for formative assessment as the technique was effective and appropriate on the students in learning vocabulary.Â